Analysis of the performance of strut models to simulate the seismic behaviour of masonry infills in partially infilled RC frames. (1st November 2020) - Mohamed, Hossameldeen; Romão, Xavier
Highlights: The reliability of using reduction factors to model partially infilled RC frames is reviewed. New reduction factors are proposed based on a comprehensive experimental dataset. An alternative to model partially infilled RC frames based on detailed FEM data is presented. Abstract: The proposed study analyses the performance of existing approaches to model the behaviour of partially infilled reinforced concrete (RC) frames for computationally-intense performance-based earthquake engineering applications. The study addresses the use of reduction factors that are applied to the strength and the stiffness of a fully infilled masonry wall to account for the effect of an opening and also the application of a macro-model calibration procedure proposed in previous research to the case of partial infills. Several empirical expressions defining reduction factors are analysed and their performance is compared using real experimental data for different masonry infill typologies. Additionally, new reduction factors exhibiting a better performance are also proposed. Despite the reasonable performance of approaches based on reduction factors, their limitations are discussed and the performance of an alternative macro-model calibration procedure is also analysed. The behaviour of several partially infilled RC frames is simulated using both approaches and the results are compared with the corresponding experimental data. Even though the new reduction factors that are proposed exhibit a reasonable performance, the alternative macro-model calibration procedure showed a more consistent performance and a better agreement with experimental data to simulate the effect of openings in masonry infills.